Blueberry Gall Midge on Southern Highbush Blueberry in Florida - Oscar E. Liburd; Douglas A. Phillips (EDIS, 2019)
Blueberry gall midge is a small fly native to North America that feeds on blueberries and cranberries. It can be found throughout the United States, including Florida, where its larvae feed on southern highbush blueberry and rabbiteye floral and vegetative buds. Reports of blueberry gall midge damage on southern highbush blueberry in Florida have become more common in recent years, in some cases significantly impacting yield where there was severe feeding damage to floral buds. This 3-page fact sheet written by Oscar Liburd and Doug Phillips and published by the UF/IFAS Department of Entomology and Nematology will inform growers how to scout for, identify, and control blueberry gall midge. http://edis.ifas.ufl.edu/in1239